The modern approach using the cuisenaire rods as compared with the traditional approach in the teaching of grade I arithmetic - Navares, Maria G. 1910- (s.n.], 1971)
This study was conducted to determine by experiment The comparative effectiveness of the Modern Approach using the Cuisenaire rods with that of the Traditional Method in the teaching of Grade I arithmetic. It aimed at exploring which of the two methods would elicit more pupil participation and better achievement between sexes through the comparison of results obtained from the use of the said methods. It was finally concluded that irrespective of the methods used, the groups differed little in the amount of knowledge retained.